(3eYQaI GdQLGds - (3GdeQj, GdHZOGOj, CHh RcQjG, , jMji Hf eYjf Hf Yhf Hf RjGO, J (B233 (3g`s
(3ChdgG (B:s
(3CNHQfG CHh YeQ eMeO Hf GdYHGS Hf eMeO Hf PehGf Hf Mjhjg GdNRGR bGd (B...(3bGd MOKfG jMji Hf eYjf hbjd dg Ydj Hf XHjGf abGd cPGH NHjK djS HKbI (B...s
(3BNQgG (B:s
... (3SeYJ jMji Hf eYjf jbhd (B... (3ecI adeG CMQefG bHd dj Mdd hcaQ abdJ dG hGddg hdcfj CVMj (B...(3CQGO EdG NjQG hGdMeO ddg (B. (3BNQ GdLRA GdChds
(3JHUQI GdYfhGf (B:s
(3QhGjI CMeO Hf eMeO GdaRGQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8\172s
(3gOjI GdYGQajf (B2\515s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs